2019
DOI: 10.14222/turkiyat4245
|View full text |Cite
|
Sign up to set email alerts
|

Kayıp Kent Germanicia: Lokalizasyon Problemleri Üzerine Yeni Gözlemler

Abstract: Öz Tarihi Prehistorik Dönemlere kadar uzanan Maraş; Mama, Gurgum, Antiocheia ad Taurum, Germanicia gibi önemli krallık, kent devleti ve şehirlere ev sahipliği yapmıştır. Ancak bunların lokalizasyonları hala yapılamamıştır. Bu makalede, literatürde Caesarea Germanicia Commagene veya Commagene Germanicia'sı olarak geçmekte olan Roma Dönemi antik kentinin lokalizasyonu üzerine önerilerde bulunulmuştur. Günümüzde Kahramanmaraş il merkezinin doğusunda yer alan Dulkadiroğlu ilçesindeki Antik Çağ yapılarının Germanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…It was understood that it belonged to another structure with mud-tempered rubble stone walls, different from the Early Byzantine Period structure that we dated to the 5-6 th century. The ceramic pieces found during the excavations and dated to the 11 th -13 th centuries indicate that this structure was reused in the Middle Byzantine Period (Dumankaya, 2019;Akyol et al, 2021;Ok and Dumankaya, 2022;Dumankaya, Akdağ, and Yıldırım, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was understood that it belonged to another structure with mud-tempered rubble stone walls, different from the Early Byzantine Period structure that we dated to the 5-6 th century. The ceramic pieces found during the excavations and dated to the 11 th -13 th centuries indicate that this structure was reused in the Middle Byzantine Period (Dumankaya, 2019;Akyol et al, 2021;Ok and Dumankaya, 2022;Dumankaya, Akdağ, and Yıldırım, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…It was revealed that the spread of archaeological remains is more than 150 hectares, during the research and excavations carried out by the Kahramanmaraş Museum (under the scientific consultancy of Assoc. Prof. Dr. Oktay DUMANKAYA) in the region, Although the concentration of Roman Period cultural remains in the research and excavations was remarkable, the discovery of Byzantine, Seljuk and Ottoman Period ceramic pieces indicates an uninterrupted settlement in the research area for centuries (Dumankaya, 2018a;Dumankaya, 2018b;Dumankaya, 2019;Akyol, Ok, and Dumankaya, 2021;Ok and Dumankaya, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In illicit excavations conducted in the Dulkadiro glu district in the early 2000s, remnants of Roman Period buildings were uncovered. Subsequent archaeological investigations led by the authors have revealed that these remnants are dispersed across an area of approximately 150 ha (Dumankaya, 2017) (Figure 1a,c). Given the extensive spatial distribution of these building remnants, it is posited that they likely belong to Germanicia, a significant urban center of the Roman Period.…”
Section: Archaeological and Historical Backgroundmentioning
confidence: 99%
“…Despite its importance, no definitive source providing detailed information about its localization has been identified. Consequently, assessments regarding the city location are based on data from research and excavations (Dumankaya, 2017(Dumankaya, , 2018a(Dumankaya, , 2018b(Dumankaya, , 2018c. Therefore, it is crucial to conduct comprehensive studies on all findings obtained from research and excavations.…”
Section: Archaeological and Historical Backgroundmentioning
confidence: 99%
“…228 Kahramanmaraş'ı etkileyen depremler hakkında bk. Dumankaya, 2019: 418. 229 Adak Adıbelli, 2006 Kelenderis'te DSB seramiklerinin az sayıda olması, Afrika Kırmız Astarlılarının erken örneklerinin ise hiç ele geçmemiş olması korsan baskınları nedeniyle MÖ 1. ve MS 2. yüzyıllarda ticareti olumsuz etkisinden bahsedilmektedir, bk.…”
Section: Değerlendirme Ve Sonuçunclassified